Impact of Trainings on Adoption of Chickpea (Cicer arietinum L.) Production Technology - Sirohiya, Lokesh; Singh, D. K.; Agrawal, S.K. (Indian Journal of Extension Education, 2012)
The study was conducted in Sihora block of Jabalpur district of Madhya Pradesh to identify the impact of Krishi  Vigyan Kendra (KVK) training programmes on extent of adoption of chickpea (Cicer arietinum L.) production  technology. six villages were selected randomly among chickpea cultivated villages. Out of which, 60 trained farmers and  60 untrained farmers were selected randomly from the similar village so total 120 respondents were taken for  investigation. The study revealed that trained farmers had higher extent of adoption of chickpea production technology  and untrained farmers had medium extent of adoption of chickpea production technology
Keywords: Adoption; recommended practices; economic motivation